Pengaruh Besar Butir dan Temperatur Pemanasan Pasir Cetak Terhadap Sifat Mekanis Cetakan - Delfian Prihadianto, Braam; Krisnaputra, Radhian; Darmo, Suryo; Prabowo, Aldi (P3M Politeknik Negeri Cilacap, 2021)
Casting is a manufacturing process that uses molten metal and molds to obtain a product that is closer to its final geometry. The quality of casting products is influenced by several factors and one of the important factors is the mold. The sand that is often used in making molds is resin coated sand, since this sand will bond to one another if it is heated. The research focus is determine the effects of grain size and heating temperature of resin coated sand on the mechanical properties of the mold which include compressive, shear and tensile strength. This study used an experimental method with large parameters of resin coated sand and heating temperature. From the test results, the highest compressive, shear and tensile strength values are Produced by sand with grain size less than 300 Âµm are identified.. The high heating temperature makes the bonds between the sands stronger and the strength value is higher..